Analisis Kinerja Belanja Dalam Laporan Realisasi Anggaran Pada Dinas Kebudayaan Dan Pariwisata Kab. Toraja Utara - Reman Liling Pongtasik; Marinus Ronal (Universitas Kristen Indonesia Toraja, 2023)
The primary objective of this study is to determine the performance of spending expenditure in the budget realization report at the Department of Culture and Tourism in North Toraja Regency. The method that used in this case study is Quantitative Descriptive Analysis. The data entry used in this thesis have multiple category which are Expenditure Variance Analysis Techniques, Expenditure Compatibility Analysis, Expenditure Growth Analysis and Efficiency Analysis. The outcome of this study prove that the expenditure performance in the budget realization report for the North Toraja Regency Culture and Tourism Industries which is from 2019-2021 can be seen from the expenditure variance with an average of 17.27%. According to the research of expenditure, the spending growth has an increase by 29.56% for the year 2020, meanwhile for the year 2021 the growth has an increase of 0.76%. Based on the analysis of compatibility, the spending ratio of operating expenditure it is categorized as suitable because it has an average of 72.18%. On the other hand, the capital expenditure ratio it is categorized quite relevant because it has an average of 46.48%. Thus, the analysis of expenditure efficiency it is categorized as the most satisfactory because it has an average effectiveness level which from year 2019 till 2021 reaching 84.44%.